Menguji Kinerja Kemitraan Inti-Plasma dengan Analisis Rentabilitas Usaha Peternakan Ayam Broiler - Bangkit Adil Pambela; Sri Widayanti; Eko Nurhadi (Universitas Halu Oleo, 2021)
The partnership performance of broiler chickens in the nucleus-plasma partnership pattern can be seen from the aspect of profitability, both at the core company and plasma breeders. A balanced partnership performance will create mutually beneficial and unilateral cooperation. This study aims to test the performance of the partnership by analyzing the core-plasma profitability of broiler chicken farms. This study was conducted from December 2020 to January 2021 in Kasiman District, Bojonegoro Regency, East Java. The population in this study was PT. Charoen Pokphand and all broiler bredeers who have a partnership with PT. X and the determinan of respondents is done by census. Data collected were analyzed descriptive quantitatively. The results of the study show that the profitability of the core company is in very healthy condition while the profitability of the plasma breeders is in a healthy condition so that the performance of the core and plasma partnerships in the broiler chicken farm is unilateral weight and is more profitable for the core company.Keywords: rentability; chicken; core-plasma partnership